The Effect Of Substitution Drill To The Students’ Ability In Understanding Subject-Verb Agreement In Writing Descriptive Text - Sirait, Shinta Grace Adinda; Munthe, Melda V.R; Hutabarat, Novra Melisa P. (CV Putra Publisher, 2026)
Grammar, particularly subject-verb agreement (SVA), played a crucial role in ensuring the structural accuracy of students’ writing. However, many students often found SVA difficult to master, which led to frequent errors in their sentences. In response to this problem, this research analyzed the effect of the Substitution Drill Technique as a teaching strategy to improve students’ mastery of SVA in writing descriptive texts. This study was conducted at SMP Cinta Rakyat 3 Pematangsiantar, focusing on eighth-grade students. The objective of this research was to investigate whether the Substitution Drill Technique had a significant effect on students’ ability to understand and apply SVA correctly in their writing. The design of this research was quasi-experimental with two groups: the experimental class taught using substitution drills and the control class taught with conventional methods. Both groups were given a pre-test and a post-test. The results showed that the experimental class’s mean score increased significantly from 51.74 in the pre-test to 84.52 in the post-test, while the control class only improved from 51.97 to 72.31. The independent samples t-test result confirmed a significance value of 0.000 (< 0.05), indicating that the Substitution Drill Technique significantly affected students’ mastery of SVA. Therefore, this study concluded that substitution drills were effective in enhancing students’ grammatical accuracy, particularly in applying subject-verb agreement in descriptive text writing